Validation of nursing educational technology for neurogenic bowel rehabilitation in people with spinal cord injury - Pereira Melo de Albuquerque, Geyslane; Faleiros, Fabiana; Noelle Corbo, Letícia; Sousa, Luís; Rodrigues Maia, Evanira; Sátiro Xavier de França, Inácia; Muniz da Silva, Simone Maria; Silva Coura, Alexsandro (Revista Cuidarte, 2024)
Highlights • Systematized intestinal rehabilitation maneuvers, also called conservative, can be recommended by nurses from primary to specialized care. • The role of the nurse as a knowledge multiplier is fundamental to the process of adherence and success of the intestinal re-education program. • The educational technology of this study can help reduce complications inherent to neurogenic intestine. • Educational technology uses teaching-learning resources efficiently, based on the possibility of dialogue before, during and after intestinal rehabilitation maneuvers. Introduction: Considered an unpredictable and recurring problem, Neurogenic Bowel does not resolve over time and progressively worsens, translating into a physical and psychological challenge, significantly reducing Quality of Life. Objective: To construct and validate the face and content of an educational technology for use by nurses in the rehabilitation of Neurogenic Bowel in people with Spinal Cord Injury. Materials and Methods: A methodological, quantitative study developed in two stages: the construction of an educational technology on the Canvas platform based on a literature review based on Wanda Horta’s Theory of Human Needs and its validation by expert judges. The validation process included nurses with ability in neurogenic bowel in teaching, research or care. The criterion for validation was agreement of over 80%, analyzed using the Content Validation Index and binomial test with confidence intervals of 95.00% (p<0.05). Results: The integrative literature review proved necessary for the construction of the proposed educational technology and covered characteristics of the Neurogenic Bowel, bowel emptying techniques, guidelines and the systematization of nursing care. The protocol was validated by ten expert judges who had graduated in nursing for more than 10 years (100.00%), with an average age of 41.8 years, female (60.00%) and an average training period of 18.6 years. An overall Content Validation Index of 0.96 (p≤0.001) was obtained for the items assessed (objective, content, relevance, functionality, efficiency and appearance/diagramming). Discussion: The implementation of an intestinal rehabilitation program aims, above all, to achieve frequent, regular and consistent stools in people with spinal cord injury and nurses, as multipliers of knowledge, can be facilitators in the teaching-learning process for carers, people with this condition and other members of the healthcare team. Conclusion: It can be concluded that the educational technology has been validated and could help the teaching-learning process for nurses in the clinical practice of caring for people with Neurogenic Bowel Disease. How to cite this article: Albuquerque, Geyslane Pereira Melo de; Faleiros, Fabiana; Corbo, Letícia Noelle; Souza, Luís; Maia, Evanira Rodrigues; França, Inácia Sátiro Xavier de; Bezerra, Simone Maria Muniz da Silva; Coura, Alexsandro Silva. Validation of nursing educational technology for neurogenic bowel rehabilitation in people with spinal cord injury. Revista Cuidarte. 2024;15(2):e3705. https://doi.org/10.15649/cuidarte.3705